PERAN GURU SOSIOLOGI MENINGKATKAN LITERASI INFORMASI PEMBELAJARAN SOSIOLOGI KELAS X SMAN 1 SENGAH TEMILA - Paramida, Cici; Sulistyarini, Sulistyarini; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to explain and analyze the role of sociology teacher in increasing information literacy in sociology learning at X grade students of SMAN 1 Sengah Temila. This research aimedalso to determine the teacher's role as an informant, facilitator, and director. This research used a qualitative approach with descriptive method. The results showed that (1) The role of the teacher as an informantin class X IIS A of SMAN 1 Sengah Temila in the process of learning sociology using information literacy has been done well by the teacher in the classroom, the sociology teacher always provided information on learning materials to their students. (2) The role of the teacher as the facilitator in class X of SMAN 1 Sengah Temila, the teacher in the learning process of sociology provided facilities such as textbooks, worksheets, and created a pleasant learning environment (3) The role of the teacher as the director in class X of SMAN 1 Sengah Temila, the sociology teacher often guided his students in finding correct information and accordance with the material discussed so the students did not make mistakes in finding learning material.Keywords: Information Literacy, Senior High School, Teacher’s role